2012
DOI: 10.1093/ejcts/ezs516
|View full text |Cite
|
Sign up to set email alerts
|

The size of consolidation on thin-section computed tomography is a better predictor of survival than the maximum tumour dimension in resectable lung cancer

Abstract: The maximum dimension of the consolidation was an independent unfavourable prognostic factor, regardless of the maximum tumour dimension. This could lead to the more accurate prediction of pathological lymph node metastasis with both GGO and consolidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 18 publications
6
70
2
Order By: Relevance
“…Lung adenocarcinomas detected as ground glass opacity (GGO) dominant tumors by high resolution computed tomography (CT) are associated with a good prognosis, and future pathologies are minimally invasive (1)(2)(3). Thus, patients with such tumors are candidates for observation rather than immediate resection.…”
Section: Introductionmentioning
confidence: 99%
“…Lung adenocarcinomas detected as ground glass opacity (GGO) dominant tumors by high resolution computed tomography (CT) are associated with a good prognosis, and future pathologies are minimally invasive (1)(2)(3). Thus, patients with such tumors are candidates for observation rather than immediate resection.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have consistently shown that the ground glass (or histologically the lepidic) component does not affect prognosis-it is the size of a solid (or histologically the invasive) component that matters (7)(8)(9)(10)(11)(12). The current 8 th edition of TNM stage classification assigns the T stage purely on the basis of the solid (clinical stage) or invasive (pathologic stage) component (13).…”
Section: Taking It a Step Furthermentioning
confidence: 99%
“…However, the recent use of computed tomography (CT) for the screening of lung cancer and advances in thin-section CT scans has made it possible to detect smaller and fainter lung nodules [3,4]. Moreover, several authors have suggested that lung adenocarcinomas seen as a wide area of ground-glass opacity (GGO) on CT scans are likely to be associated with a good prognosis and in most cases their pathologic features are minimally invasive [5][6][7][8][9]. Thus, patients with these tumors are considered as candidates for limited surgical resection, as confirmed by the prospective JCOG 0201 study in Japan [10].…”
Section: Introductionmentioning
confidence: 99%